Dermoscopy-guided carbon dioxide laser destruction for nevus sebaceous: two case reports - Wibawa, Larisa Paramitha; Ohara, Kuniaki (UI Scholars Hub, 2021)
Background: Nevus sebaceous (NS) is a common hamartoma of the cutaneous adnexal structure, clinically appear as a well demarcated yellow-orange plaque, sometimes with verrucous surface. Dermoscopy may aid the diagnosis of NS and also guide carbon dioxide (CO2) laser therapy. Case Illustration: Two cases of brown and yellowish plaque on the face, with clinical appearance, dermoscopic, and histopathological findings consistent with NS. The patients consented to undergo serial CO2laser destruction, aimed to reduce recurrences and shorten the duration of the downtime. Dermoscopy aided in locating the area and the depth of each treatment. Discussion: The dermoscopy finding of NS were already reported as milia-like structure and multiple whitish structures (dots) varying in size, with orange background. The dermoscopy findings of these two cases were in accordance with previous reports. CO2laser destruction was reported to produce satisfying results, but with known recurrences. With the knowledge of dermoscopy appearance, we could determine the area and depth of the lesion to prevent reoccurrence. After two years of follow-up, the area where the deep ablation was performed had not reoccurred. Conclusion: Dermoscopy may aid the diagnosis and therapeutic confirmation of NS.